Outer Plexiform Layer Structures Are Not Altered Following AAV-Mediated Gene Transfer in Healthy Rat Retina - Giers, Bert C.; Klein, Daniela; Mendes-Madeira, Alexandra; Isiegas, Carolina; Lorenz, Birgit; Haverkamp, Silke; Stieger, Knut (Frontiers in Neurology, 2017)
Ocular gene therapy approaches have been developed for a variety of different diseases. In particular, clinical gene therapy trials for RPE65 mutations, X-linked retinoschisis and choroideremia have been conducted at different centres in recent years, showing that AAV-mediated gene therapy is safe, but limitations exist as to the therapeutic benefit and long term duration of the treatment. The technique of vector delivery to retinal cells relies on subretinal injection of the vector solution, causing a transient retinal detachment. Although retinal detachments are known to cause remodelling of retinal neuronal structures as well as significant cell loss, the possible effects of this short-term therapeutic retinal detachment on retinal structure and circuitry have not yet been studied in detail. In this study, retinal morphology and apoptotic status were examined in healthy rat retinas following AAV-mediated gene transfer via subretinal injection with AAV2/5.CMV.d2GFP or sham-injection with fluorescein. Outer plexiform layer (OPL) morphology was assessed by immunohistochemical labeling, laser scanning confocal microscopy, and electron microscopy. The number of synaptic contacts in the OPL was quantified after labeling with structural markers. To assess the apoptotic status, inflammatory and pro-apoptotic markers were tested and TUNEL-Assay for the detection of apoptotic nuclei was performed. Pre- and postsynaptic structures in the OPL, such as synaptic ribbons or horizontal and bipolar cell processes, did not differ in size or shape in injected versus non-injected areas and control retinas. Absolute numbers of synaptic ribbons were not altered. No signs of relevant gliosis were detected. TUNEL labeling of retinal cells did not vary between injected and non-injected areas and apoptosis inducing factor (AIF) was not delocalized to the nucleus in transduced areas. The neuronal circuits in the OPL of healthy rat retinas undergoing AAV mediated gene transfer were not altered by the temporary retinal detachment caused by subretinal injection, the presence of viral particles or the expression of GFP as a transgene. This observation likely requires further investigations in the dog model for RPE65 deficiency in order to determine the impact of RPE65 transgene expression on diseased retinas in animals and men.